Implementasi Metode Inquiry dalam Pembelajaran Pendidikan Agama Islam guna Meningkatkan Kualitas Hasil Belajar Siswa di Sekolah Menengah Pertama - Novia Nurshibah; Oyoh Bariah; Nancy Riana (Jurnal Pendidikan Tambusai, 2022)
Islamic religious education is one area of ??learning that cannot be realized instantly, but Islamic religious education is an important part that must be instilled in the Muslim generation from an early age. The rapid development of time and technology needs to be balanced with the planting of stronger Islamic religious education. Therefore, conventional learning methods that are no longer relevant to the developments and needs of the times should be developed and collaborated with learning methods that can provide facilities for students to develop their minds to be able to come up with ideas and find solutions to problems that occur, one of which is the application of the inquiry method. . This study aims to examine the application of the inquiry method in the learning process of Islamic Religious Education by using a descriptive qualitative approach. The results of the study indicate that the inquiry method is a learning centered on the scientific attitude of students in deciding the problems at hand, so that the speculations or ideas found can be applied in the field. The characteristics of inquiry learning are critical thinking, facilitating, flexible, based on interdisciplinary methodologies, openness, problem solving, personal responsibility, and self-regulation. Able to encourage students to think more critically and not limit students' creative space in reasoning lessons. The application of this method is the teacher as a facilitator in determining the theme of learning and students think actively and creatively in solving all problems in learning. This method is very effective as an alternative to solve problems in a problem and in the learning process of Islamic Religious Education for junior high school children.